Avaliação do impacto da urbanização sobre o escoamento superficial na bacia do Córrego do Barbado, Cuiabá-MT - Colet, Karina Marcondes (2012)
The purpose of this study is highlight the changes in hydrological dynamics in the urban area due the rapid population growth. Thus, this study aims to evaluate the impact of urbanization on the hydrological dynamics catchments stream Barbados by means the elaboration of Environmental Quality Indices (EQI), estimation of runoff and the environmental diagnosis to check the current status of conservation of Permanent Preservation Areas stream (PPA). The results showed that the Green Area Index (GAI), Percentage of Green Areas (PGA), Index of Public Spaces (IPS) and Percentage of Public Spaces (PPE) of the catchments are low compared to other localities, indicating the need to expand green areas. The hydrological simulations indicate planning solutions that mitigate runoff, need mitigate runoff, as with urban growth, the drainage systems can not support the surfaces flow demand. The environmental diagnosis revealed that the stream has serious degradation factors.